Can poetry help GPs and GP trainees to develop their reflective practice?. Issue 6 (June 2022) - Whittle, Bethany; Macgregor, Kirsty; Cooper, Max; Sornalingam, Sangeetha; Okorie, Michael
Fostering reflective practice is an integral part of continuing professional development and general practice training. However, popular reflective tools are often applied superficially, with little insight generated as a result. This article presents engagement with poetry as a unique method of reflection, which can enable clinicians to reflect on challenging experiences including those encountered during the COVID-19 pandemic. Existing communities who use poetry as a reflective tool will be spotlighted. Finally, the impact of poetic reflection in building resilience and mature reflection for GPs and GP trainees will be considered.